A Malay-English cross-linguistic study of present time forms - Mohammad Lotfie, Maskanah (IIUM Press, 2011)
This is a comparative study of written present time forms of Malay and English. Central to the discussion on temporal similarities and differences between the two languages is the unmarked form of the former. Written output from Malay and English as a second language (ESL) respondents were collected and the data analysis provides evidence of the difference in the acquisitional patterns of the English present time forms between the two distinct levels of Malay users of the English language. Lower intermediate users’ output strongly approximates Malay forms while the more proficient group’s interlanguage indicates the usage of more complex linguistic items.